138: Respiratory Illness and Respiratory Syncytial Virus Hospitalizations in Infants with Congenital Airway Anomalies in the Canadian Registry of Synagis® Following Prophylaxis (2005–2013). Issue 6 (1st June 2014) - Paes, B; Li, A; Mitchell, I; Lanctot, KL
Abstract: BACKGROUND: Palivizumab is recommended by national and international pediatric advisory committees for the prevention of respiratory syncytial virus (RSV) infection and subsequent related hospitalization in high-risk infants. The CARESS registry tracks palivizumab use and respiratory outcomes in such infants, including those with congenital airway anomalies (CAA). OBJECTIVES: The primary objective of this study is to compare hazards for hospitalization for respiratory illness (RIH) and RSV positive infection (RSVH) in CAA infants versus those prophylaxed for other pre-existing medical illnesses (MI) and standard indications (SI). DESIGN/METHODS: Infants who received ≥1 dose of palivizumab during the 2005–2013 RSV seasons were recruited from 32 Canadian sites and followed prospectively. The MI group included a spectrum of infants with underlying disorders such as cystic fibrosis, neuromuscular impairments, Down syndrome and immune-compromised individuals. The SI group comprised preterm infants (≤35 weeks gestational age who were <6 months at the start of the RSV season) and those aged <2 years with either chronic lung disease (bronchopulmonary dysplasia) or infants with hemodynamically significant congenital heart disease. Palivizumab utilization and hospitalization outcomes were collected monthly throughout respective seasons. A Cox proportional hazard analysis adjusting for risk factors compared hazard ratios (HR) across prophylaxis indications. RESULTS: 16, 290 infants were enrolled (447 CAA; 2120 MI; 13, 723 SI). Infants received an average of 90.5±18.2% of their expected injections, and no significant differences (P<0.05) were seen across groups (F[2, 16268]=2.66; P=0.07). Adjusting for significant (P<0.05) group differences (enrolment age, having siblings, aboriginal origin and multiple birth status) showed CAA infants had a significantly higher hazard of RIH (HR [95% CI]; P value) compared to MI (1.59 [95% C1.03 to 2.44]; P=0.03) and SI (95% C1.85 [95% C1.27 to 2.69]; P=0.001). However, the CAA group had a similar HR for RSVH compared to MI (2.15 [95% C0.75 to 6.21]; P=0.16) and SI (2.28 [95% C0.92 to 5.659]; P=0.08), but other risk factors remained significant (P<0.05). CONCLUSIONS: This is the largest report of CAA infants who have received palivizumab world-wide. CAA infants have an increased hazard for RIH compared to MI and SI but appear to have a similar RSVH hazard despite differences in risk factors.